Upaya Peningkatan Pendapatan Keluarga Melalui Budidaya Ikan dan Sayuran Dalam Ember Di Kelurahan Kandang Limun - Esti Pasaribu; Yefriza; Bima Prasetya Kumara (UNIB Press, 2026)
This community service program aims to enhance the knowledge and skills of housewives in applying the technology of fish and vegetable cultivation in buckets (budikdamber) as an effort to increase household income and strengthen food self-sufficiency. The implementation methods include a preparation stage through surveys and field observations, coordination with village officials and community leaders, and an implementation stage consisting of counseling, discussion, and demonstration of budikdamber techniques for 20 housewives who are members of a local religious study group in Kandang Limun. The results show high enthusiasm and active participation among the participants, improved understanding of how to cultivate catfish and vegetables in buckets, and increased motivation to start small-scale home-based enterprises using budikdamber. This activity has the potential to strengthen household food security and provide an alternative source of supplementary income for poor and underemployed urban households. Thus, budikdamber can be recommended as a simple, low-cost, and applicable model of household economic empowerment in densely populated residential areas with limited land availability.